Can EEG Predict Response to Atomoxetine in attention deficit hyperactivity disorder at 1 Week?. Issue 5 (March 2021) - Singh, Gurmukh; Arun, Priti; Das, Subhash; Kaur, Damanjeet
Objective: The objective of the study is to predict the early changes in electroencephalography (EEG) at 1 week and its correlation to clinical response at 6 weeks after treatment with atomoxetine in children with ADHD.Method: In 50 children (6-14 years) with ADHD ( Diagnostic and Statistical Manual of Mental Disorders [5th ed.; DSM-5 ]), Vanderbilt ADHD Parent Rating Scale (VADPRS) and Vanderbilt ADHD Teachers Rating Scale (VADTRS) were applied at baseline, 1, 4, and 6 weeks. EEG was recorded using International 10–20 System of electrode placement at baseline and at 1 week after atomoxetine treatment. EEG changes at 1 week after atomoxetine therapy was correlated to clinical response at 6 weeks.Results: Patients were classified as responders or nonresponders based on the VADPRS/VADTRS findings. After 1 week of treatment, responders' theta cordance values were decreased, whereas nonresponders' values didn't decrease significantly.Conclusion: Patients with decreased theta cordance values, especially in the left temporoparietal region, at 1 week were likely to respond to atomoxetine while those without any such change were likely to be nonresponders.